Diagnosis and impact of neuropathic pain in leprosy patients in Nepal after completion of multidrug therapy. - Han-Siong Toh; Jeni Maharjan; Ruby Thapa; Kapil Dev Neupane; Mahesh Shah; Suwash Baral; Deanna A Hagge; Indra Bahadur Napit; Diana N J Lockwood (Public Library of Science (PLoS), 2018)
Neuropathic pain (NP) can occur as a chronic complication of leprosy neuropathy. NP epidemiology and its impact on patients have not been well documented. This study investigates NP prevalence and impact in the years after patients are declared "released from treatment" (RFT) following multidrug therapy (MDT) completion.In this cross-sectional study, 85 RFT patients were recruited within leprosy referral services in Nepal. The Douleur Neuropathique 4 Questionnaire (DN4) was used to screen for NP. Pain severity, impacts on patients' daily activities and mental health were measured by using the Brief Pain Inventory (BPI), Screening of Activity Limitation and Safety Awareness (SALSA), and General Health Questionnaire-12 (GHQ-12) respectively.96% surveyed had been treated for multibacillary leprosy. 44 (52%) complained of pain of which 30 (68%) were diagnosed with NP. NP was not associated with age, gender, or presence of skin lesions or nerve symptoms at leprosy diagnosis. 70% of patients with NP had either history of or ongoing reactions and 47% had grade 2 disability. Nerve tenderness (p = 0.023) and current reactions (p = 0.018) were significant risk factors for NP. Patients with NP suffered significantly higher intensity pain (p = 0.023) and daily life interference (p = 0.003) and were more likely to have moderate to extreme daily activity limitations (p = 0.005). 13 (43%) exhibited psychological distress, and medications only reduced moderate degree (50-60%) of pain.In our study, 35% of RFT patients had ongoing NP. Risk factors include nerve tenderness and reaction. They suffer from more daily life interference and psychological distress. Leprosy patient care should include recognition and management of NP.